Implementación de antena leaky-wave basada en metasuperficie de Huygens - Abdo-Sánchez, María Elena; Epstein, Ariel; Eleftheriades, George V. (My University, 2018)
In this communication, the implementation of a leaky-wave antenna based on bianisotropic Huygens’ metasurface is addressed. It consists of a parallel-plate waveguide in which the top plate is replaced by a metasurface. It was previously shown that, by properly designing the metasurface, arbitrary control on the radiation parameters of the leaky mode can be achieved. Closed-form expressions allow getting the constitutive parameters of the required metasurface. However, achieving a physical realization entails several challenges, discussed in this contribution.
Keywords: Radio - Antenas - Congresos; Antena; Leaky-wave; Metasuperficie de Huygens; Transformación de campo; Radiación